RIFM fragrance ingredient safety assessment, hydroxycitronellal dimethyl acetal, CAS Registry Number 141-92-4. (December 2019) - Api, A.M.; Belmonte, F.; Belsito, D.; Biserta, S.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Cancellieri, M.A.; Dagli, M.L.; Date, M.; Dekant, W.; et al.
Abstract: Hydroxycitronellal dimethyl acetal was evaluated for genotoxicity, repeated dose toxicity, reproductive toxicity, local respiratory toxicity, phototoxicity/photoallergenicity, skin sensitization, and environmental safety. Data from read-across analog hydroxycitronellal diethyl acetal (CAS # 7779-94-4) show that hydroxycitronellal dimethyl acetal is not expected to be genotoxic. The repeated dose, reproductive, and local respiratory toxicity endpoints were evaluated using the TTC for a Cramer Class I material and the exposure to hydroxycitronellal dimethyl acetal is below the TTC (0.03 mg/kg/day, 0.03 mg/kg/day, and 1.4 mg/day, respectively). Data from hydroxycitronellal dimethyl acetal and from read-across material hydroxycitronellal diethyl acetal (CAS # 7779-94-4) show that there are no safety concerns for skin sensitization under the current declared levels of use. The phototoxicity/photoallergenicity endpoints were evaluated based on UV spectra; hydroxycitronellal dimethyl acetal is not expected to be phototoxic/photoallergenic. The environmental endpoints were evaluated; hydroxycitronellal dimethyl acetal was found not to be PBT as per the IFRA Environmental Standards, and its risk quotients, based on its current volume of use in Europe and North America (i.e., PEC/PNEC), are <1. Highlights: Hydroxycitronellal dimethyl acetal; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.